GeoSmart Application as a Tool for Interactive Learning: Literature Review Completed with Experiments for Improving Understanding of Geospheric Phenomena in Geography Education - Fadjarajani, Siti; As’ari, Ruli; Ningrum, Epon; Ahmad, Mohammad Zohir (ASEAN Journal of Science and Engineering, 2024)
This study creates and tests the GeoSmart app as an interactive learning tool for high school students to understand geospheric phenomena. The research encompassed concept creation, design, material acquisition, assembly, testing, and dissemination. The study involved a planned group of high school students from Tasikmalaya City. We administered questionnaires and comprehension tests both before and after using the app to collect data. The program significantly improved students' understanding of geospheric phenomena. Statistics verified these benefits, showing that GeoSmart's interactive features engage students and help them understand complicated subjects. The findings suggest that the GeoSmart application has considerable potential for broader adoption in geography education, as it effectively enhances both learning quality and student motivation. This study stresses how important technology is in education and suggests more research be done to look into the long-term effects and wider use of GeoSmart apps.